(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2006)
In the previous edition of Existential Analysis, I summarised the existing literature on physicians’ emotional and behavioural responses to their patients’ deaths. That literature led me to the following general conclusions: (1) physicians often experience grief, anxiety, and/or trauma when faced with the death of a patient under their care; and (2) medical training programmes, professional colleagues, superiors, patients, and society at large all expect physicians to suppress – or simply not experience – those reactions. This paper bolsters those conclusions by presenting some of the results of a small-scale phenomenological investigation of eight physicians’ own experiences with patient death.